Perancangan UI/UX Website Pengenalan Budaya Bali dengan Metode User Centered Design - Santiani, Ida Ayu Made Putri; Supriana, I Wayan (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 4 (2024): JNATIA Vol. 2, No. 4, Agustus 2024DO - 10.24843/JNATIA.2024.v02.i04.p17, 2024)
Culture is a collection of beliefs and traditions passed down from generation to generation by a group of people. The island of Bali is one of the places rich in culture and traditions. Each district in Bali has its own unique culture and traditions. This cultural diversity and tradition serve as an attraction for domestic and international tourists who want to visit the island of Bali. To help tourists get to know more about Balinese culture and find places to eat according to their preferences, this research aims to develop a website-based application. This website is developed using the User-Centered Design method. This website can be a solution for tourists who want to visit Bali to see local traditions and culture or enjoy the typical dishes found on the island of Bali.